Child abuse and neglect profiles and their psychosocial consequences in a large sample of incarcerated males. (March 2017) - Debowska, Agata; Boduszek, Daniel
Abstract: Research examining child abuse and neglect (CAN) profiles among adult offender populations is lacking. Therefore, the primary aim of the present study was to address this limitation by using latent class analysis (LCA) to identify meaningful classes of individuals who have experienced physical abuse, emotional abuse, sexual abuse, as well as neglect. Another aim was to estimate the association between CAN class membership and external criteria (psychopathy factors, self-esteem, attitudes towards male sexual violence in dating relationships, child sexual abuse myth acceptance, violent offending, and age). Data were collected among a large systematically selected sample of adult male inmates ( N  = 1261). Based on LCA, three unique classes of CAN were distinguished, including a 'low abuse' group (43.4% of the sample), a 'high physical and emotional abuse' group (51.3%), and a 'poly-victimized' group (5.3%). The analysis revealed that the CAN classes were differentially associated with affective responsiveness, cognitive responsiveness, personal self-esteem, prison self-esteem, attitudes towards male sexual violence in dating relationships, and violent offending. Findings highlight the unique nature of CAN constellations among criminal justice involved participants. The significance of the present results is discussed in relation to past and future research. Potential contributions to treatment strategies are also presented.